Emerging Catalyst Control in Cobalt-Catalyzed Oxidative Hydrofunctionalization Reactions - Zhu, Rong (Synlett, 2019)
Oxidative functionalization has emerged as an important pathway in Co-catalyzed hydrogen atom transfer (HAT) hydrofunctionalization reactions. Notably, evidence was found for the participation of organometallic intermediates in such radical-polar crossover processes. These findings provide opportunities for catalyst control that was previously absent in HAT catalysis. In this article, we summarize the recent progress towards this direction involving carbon–heteroatom bond-forming intra- and intermolecular reactions, including work from our own group.1 Introduction2 Oxidative Trapping by Solvents and Intramolecular Nucleophiles3 Intermolecular Oxidative Hydrofunctionalization4 Conclusion and Outlook
Keywords: cobalt; radicals; hydrofunctionalization; iodine; catalysis; hydrogen atom transfer